GEL criteria for moment condition models - Richard J. Smith (Centre for Microdata Methods and Practice (cemmap), 2004)
GEL methods which generalize and extend previous contributions are defined and analysed for moment condition models specified in terms of weakly dependent data. These procedures offer alternative one-step estimators and tests that are asymptotically equivalent to their efficient two-step GMM counterparts. The basis for GEL estimation is via a smoothed version of the moment indicators using kernel function weights which incorporate a bandwidth parameter. Examples for the choice of bandwidth parameter and kernel function are provided. Efficient moment estimators based on implied probabilities derived from the GEL method are proposed, a special case of which is estimation of the stationary distribution of the data. The paper also presents a unified set of test statistics for over-identifying moment restrictions and combinations of parametric and moment restriction hypotheses.
Keywords: C13; C30; 330; GMM; Generalized Empirical Likelihood; Efficient Moment Estimation; Overidentifying Moments; Parametric Restrictions; Additional Moment Restrictions; Schätztheorie; Momentenmethode